Comparison of transport methods for plastics from Belgium to Sweden Alternatives, costs, environmental impacts and price of transport services - Thiringer, Carl (My University, 2022)
In this work the C02 emission and cost has been determined for transport of plastic scrap from Antwerpen, Belgium to Smålandsstenar, Sweden. Boat, rail and truck transports have been investigated as well as combinations of these transport modes. The CO2 emission both for transport and for electric power generation as well as the cost has been determined through literature searching as well as in interviews with transport companies. It was found that the train transportation was the one giving lowest CO2 emission. Boat transport also turned out to be rather environmentally friendly as well. Regarding the cost, it turned out that it was fairly equal, in the range of 18000-24000 kr per container.
Keywords: train, truck, boat, transport, CO2 emission, freight, intermodal